2010
DOI: 10.1007/s12185-010-0736-0
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIII concentration is greater in female than male patients with HIV infection

Abstract: The purpose of the present study was comparing plasma markers of coagulation between men and women in both HIV-infected patients and controls. Fifty-eight HIV-infected patients and 58 healthy participants who were individually matched with patients in age and sex were included in the study. We simultaneously collected blood samples for CD4+ T cell count, CD8+ T cell count, platelets count, hemoglobin, partial thromboplastin time (PTT), prothrombin time, international normalized ratio and blood type measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Our results were similar to another analysis from the WIHS study which showed decreases in Protein S and increases in factor VIII among women with advancing HIV disease compared to controls 22 , and a study by Abdollahi et al showing greater Factor VIII and decreased Protein S in HIV-infected patients compared to controls in Tehran, Iran 97 . Trotti et al showed significantly higher levels of PAI-1 in a small number of HIV infected patients compared to healthy controls 17 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results were similar to another analysis from the WIHS study which showed decreases in Protein S and increases in factor VIII among women with advancing HIV disease compared to controls 22 , and a study by Abdollahi et al showing greater Factor VIII and decreased Protein S in HIV-infected patients compared to controls in Tehran, Iran 97 . Trotti et al showed significantly higher levels of PAI-1 in a small number of HIV infected patients compared to healthy controls 17 .…”
Section: Discussionsupporting
confidence: 91%
“…HIV has known associations with the markers of hemostasis measured here 17–19,21,23,97,98 . Our results were similar to another analysis from the WIHS study which showed decreases in Protein S and increases in factor VIII among women with advancing HIV disease compared to controls 22 , and a study by Abdollahi et al showing greater Factor VIII and decreased Protein S in HIV-infected patients compared to controls in Tehran, Iran 97 .…”
Section: Discussionmentioning
confidence: 88%
“…PKA does not appear to inhibit NF-κB-driven transcription by disrupting IkBα degradation or NF-κB DNA binding activity ( Takahashi et al, 2002 ). Rather, NF-κB transcriptional activity may be inhibited either directly, through phosphorylation of the NF-κB subunit, p65, on serine 536 of the C-terminal transactivation domain (p-p65) ( Takahashi et al, 2002 ) and blocking p65 nuclear translocation ( Abdollahi et al, 2011 ), or indirectly, through phosphorylation and competition for the transcriptional coactivator CREB binding protein (CBP), or its homologue, p300 ( Parry and Mackman, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fibrinogen levels have been shown to be similar between treated and untreated HIV infected persons and controls [ 13 – 15 ]. Regarding anticoagulant factors, treated and untreated HIV infected persons have been shown to have lower levels of protein S and protein C than uninfected controls [ 10 , 16 ] and untreated HIV infected persons have lower levels than treated [ 17 ]. Further, untreated HIV infected persons show signs of increased fibrinolysis with increased d-dimer [ 15 ] and some studies find persistently elevated levels after cART [ 18 ] whereas others find normalization of D-dimer with cART [ 10 ].…”
Section: Introductionmentioning
confidence: 99%